A co-culture model to study modulators of tumor immune evasion through scalable arrayed CRISPR-interference screens - Martinez, Ramiro; Finocchiaro, Chiara; Delhaye, Louis; Gysens, Fien; Anckaert, Jasper; Trypsteen, Wim; Versteven, Maarten; Lion, Eva; Van Lint, Sandra; Vermaelen, Karim; de Bony, Eric James; Mestdagh, Pieter (Frontiers in Immunology, 2024)
Cancer cells effectively evade immune surveillance, not only through the well-known PD-1/PD-L1 pathway but also via alternative mechanisms that impair patient response to immune checkpoint inhibitors. We present a novel co-culture model that pairs a reporter T-cell line with different melanoma cell lines that have varying immune evasion characteristics. We developed a scalable high-throughput lentiviral arrayed CRISPR interference (CRISPRi) screening protocol to conduct gene perturbations in both T-cells and melanoma cells, enabling the identification of genes that modulate tumor immune evasion. Our study functionally validates the co-culture model system and demonstrates the performance of the CRISPRi-screening protocol by modulating the expression of known regulators of tumor immunity. Together, our work provides a robust framework for future research aimed at systematically exploring mechanisms of tumor immune evasion.A co-culture model to study modulators of tumor immune evasion through scalable arrayed CRISPR-interference screens 2 Material and MethodsA co-culture model to study modulators of tumor immune evasion through scalable arrayed CRISPR-interference screensA co-culture model to study modulators of tumor immune evasion through scalable arrayed CRISPR-interference screensA co-culture model to study modulators of tumor immune evasion through scalable arrayed CRISPR-interference screens